Asymmetric electron acceptor enables highly luminescent organic solar cells with certified efficiency over 18 - He, Chengliang; Chen, Zeng; Wang, Tonghui; Shen, Ziqiu; Li, Yaokai; Zhou, Jiadong; Yu, Jianwei; Fang, Huiyu; Li, Yuhao; Li, Shuixing; Lu, Xinhui; Ma, Wei; et al. (Nature communications, 2022)
Enhancing the luminescence property without sacrificing the charge collection is one key to high-performance organic solar cells (OSCs), while limited by the severe non-radiative charge recombination. Here, we demonstrate efficient OSCs with high luminescence via the design and synthesis of an asymmetric non-fullerene acceptor, BO-5Cl. Blending BO-5Cl with the PM6 donor leads to a record-high electroluminescence external quantum efficiency of 0.1%, which results in a low non-radiative voltage loss of 0.178 eV and a power conversion efficiency (PCE) over 15%. Importantly, incorporating BO-5Cl as the third component into a widely-studied donor:acceptor (D:A) blend, PM6:BO-4Cl, allows device displaying a high certified PCE of 18.2%. Our joint experimental and theoretical studies unveil that more diverse D:A interfacial conformations formed by asymmetric acceptor induce optimized blend interfacial energetics, which contributes to the improved device performance via balancing charge generation and recombination. High-performance organic solar cells call for novel designs of acceptor molecules. Here, He et al. design and synthesize a non-fullerene acceptor with an asymmetric structure for diverse donor:acceptor interfacial conformations and report a certificated power conversion efficiency of 18.2%.